2014
DOI: 10.1002/qre.1664
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Tukey's and Individual/Moving Range Control Charts

Abstract: This paper compares two control charts: Tukey (TCC) and individual/moving range (XmR) control charts. Both are designed to examine single observation per time period, but little is known about which one is more efficient and under what conditions. We simulated data from different distributions and examined the performance of the two control charts on these data. Performance was assessed using the of average run length, extra quadratic loss, median run length, standard deviation run length, performance comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…These run length properties may be calculated by using the following expressions (cf. Chakraborti [26], Khaliq et al [27])…”
Section: Performance Evaluation Techniquesmentioning
confidence: 97%
“…These run length properties may be calculated by using the following expressions (cf. Chakraborti [26], Khaliq et al [27])…”
Section: Performance Evaluation Techniquesmentioning
confidence: 97%
“…Khaliq at el. [10] did the comparative analysis to judge the performance of Tukey chart versus X/MR chart under the several probability models and Tukey chart was the best choice in many cases. The study revealed that this charts is a good alternative to Shewhart and X/MR chart for monitoring when data is of skewed form.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has an effective charting structure that exhibits robustness for the skewed distributions. Alemi and several other authors have studied its properties such as Khaliq et al , Lee et al , Torng and Lee, Lee and Torng, Tercero‐Gomez et al , and Torng et al , among many others. The control limits for this chart are defined a LCL=Q1L()IQR,0.24emCL=Q2,0.24emUCL=Q3+L()IQR where Q 1 and Q 3 are the first and third quartiles, Q 2 is the median, IQR is deviation of Q 1 and Q 3 , i.e., inter‐quartile range (IQR) is defined by Q 3 −Q 1 , and L is the control limits coefficient that may be fixed at a pre‐specified value of average run length (ARL), denoted by ARL 0 for an in‐control process.…”
Section: Design Of Tukey‐cusum Control Chartmentioning
confidence: 99%
“…It has an effective charting structure that exhibits robustness for the skewed distributions. Alemi 1 and several other authors have studied its properties such as Khaliq et al, 10 Lee et al, 12 Torng and Lee, 32 Lee and Torng, 13 Tercero-Gomez et al, 31 and Torng et al, 33 among many others. The control limits for this chart are defined a…”
Section: Tukey's Control Chartmentioning
confidence: 99%
See 1 more Smart Citation